Live Versus Video-Recorded Student Presentations: A Convergent Mixed-Methods Study of Confidence, Anxiety, and Engagement in Higher Education - Masrurotul Ajiza; Feny Arafah (Journal of Educational Research and Practice, 2026)
This study used convergent mixed-methods to investigate whether live presentations and video-recorded presentations differentially affected undergraduate students' presentation confidence and anxiety and their level of engagement with presentations. A total of 35 students completed both a live and an edited video presentation; researchers used validated Likert scales to measure quantitative outcomes, which they analyzed through paired tests in JASP and thematic analysis of written reflections in NVivo. The video format produced increased task-specific confidence according to quantitative analysis, which showed a difference of 2.29, a large standardized effect size of 0.89, and a p-value below .001. The analysis revealed that no significant differences existed between the two presentation formats concerning presentation anxiety (paired t = 1.26, p = .216) or engagement (paired t = −1.36, p = .183); nonparametric analyses returned consistent results. The qualitative analysis of 35 reflections found six main themes, which included rehearsal and control, real-time interaction and feedback, technical workload, perceived fairness, affective effects, and logistics; the analysis showed that 26 participants linked rehearsal/control to increased confidence, while 24 participants showed the same link. The joint display connected the quantitative and qualitative data: the video condition provided confidence gains, which related to the students' reported chances for rehearsal and revision. At the same time, their anxiety and engagement levels changed based on their interactional and logistical circumstances. The research demonstrates how Self-Efficacy Theory applies to controlled mastery chances between recording and editing, leading to improved performance in specific tasks, while Social Presence Theory shows how people face choices between two options that affect their personal contact with others and the process of performance assessment. The practical implications require institutions to establish organized recording practice spaces, which create fairness in assessment through separate content assessment from production quality assessment. At the same time, they need to help students with technical problems to create equity in educational outcomes.